Blockchain-Based Distributed Renewable Energy Management Framework - Shikah J. Alsunaidi; Fakhri Alam Khan (IEEE Access, 2022)
Most of the world’s countries are concerned with reducing harmful gas emissions. Some governments have made considerable attempts to address this problem. Saudi Arabia, for example, has taken significant steps to utilize renewable energy (RE) sources in addition to oil and gas. Consumers are encouraged to build small RE systems. These small grids will help people meet their daily electrical energy requirements. They can sell the excess to other customers. One of the major issues is managing the distribution and sale of RE. Blockchain-based peer-to-peer (P2P) networks can help overcome several obstacles to the implementation of a distributed RE management system (DREMS). However, several impediments may still stand in the way of its execution. Scalability and productivity are two of the most important considerations. The number of transactions made to the Blockchain network will increase in lockstep with the number of energy consumers. This will result in a significant lag in response. Understanding the renewable distributed energy system will aid in minimizing the effects of these roadblocks. Therefore, this research identifies the RE systems installation approaches, and how Blockchain technology can be utilized. It provides the solution requirements of any DREMS. Moreover, it proposes a new Blockchain-based framework for DREMS. And designs selective protocols of the proposed framework. It provides a comparative analysis to assess the proposed protocols’ ability to meet the identified requirements.